The Hadiths of Neuroscience: A Hermeneutic Study on the Prophet's Sunnah in Thinking Framework - Husna, Jannatul; Suyadi, Suyadi (Institut Agama Islam Negeri (IAIN) Curup, 2024)
The sciences that study reason, thinking, or the brain are known as neuroscience in modern science. The interpretation of neuroscience verses in the Quran has developed rather significantly. However, similar studies of the Prophet's hadith still have little. Therefore, this study aims to discover the hadiths of neuroscience and analyze them with a hermeneutic approach. This research is a literature review with primary data sources from seven books of hadith and other relevant texts. The study found five hadiths in Sunan Abi Dawud, Musnad Ahmad, al-‘Azamah, Musnad al-Harith, and others that emphasize the Prophet’s sunnah in thinking. The author mentions the five hadiths as neuroscience hadiths: 1) differences in common sense and loss of reason in the Sunan Abi Dawud, of good quality; 2) the urgency of ijtihad in the Sunan Abi Dawud, of good quality; 3) intelligent and ignorant differences in the Musnad Ahmad, hasan quality; 4) limitations of the capacity of human reason in the al-‘Azamah as hasan li ghairihi; and 5) the position of reason in the Musnad al-Harith of da’if jiddan. The findings of these neuroscience hadiths allow them to grow steadily and potentially become a new landscape in the future. Complements the study of the interpretation of neuroscience verses that have developed earlier.